Legislative requirements related to substrate depth as a barrier to the construction of green roofs in Bulgaria - Mariam Bozhilova; Miglena Zhiyanski; Plamen Glogov (Silva Balcanica, 2020)
There are 265 municipalities in Bulgaria. According to the national legislation, each Municipal Coun-cil adopts an Ordinance for the construction and protection of the green system. Most of the mu-nicipalities have such ordinances, however, only 75 of them stipulate regulative requirements, under which a green roof can be considered a green area. These requirements refer to the substrate depth and are unreasonably high. While positive impacts are reported in green roofs with a substrate layer thickness of 4 – 5 cm, green roofs with substrate depth under 10 cm are not considered a green area in any of the reviewed ordinances. One municipality considers green roofs with substrate 10-30 cm as a green area, under specific conditions. This paper provides a review of the stipulations of the Bulgarian local legislation against the existing data for the effects of green roofs with different substrate depths and outlines the need for amendment of the legislation and future research.